Development of polyclonal antibodies-based serological methods and a DIG-labelled DNA probe-based molecular method for detection of the Vicia cryptic virus-M in field plants - Zhang, K.; Zhuang, X.; Xu, H.; Gan, H.; He, Z.; Chen, J.
Vicia cryptic virus M (VCV-M), a member of the genus Amalgavirus of the family Amalgaviridae, was first identified in 2009 in a Vicia faba Linn. planting in Hangzhou, Zhejiang Province, China. However, there has been no further research on the biological features of VCV-M to date and the viral particles and coat protein (CP)have not been identified. The putative CP of VCV-M was predicted from the viral genomic RNA. In this study, a recombinant version of the putative CP of VCV-M (His-CPVCV-M)was produced and used to prepare a polyclonal antiserum against the His-CPVCV-M. Using this antiserum, a Western blot, an immuno-dot-blot and an enzyme-linked immunosorbent assay were developed for testing field samples of V. faba for the presence of VCV-M. Additionally, a digoxigenin (DIG)-labelled DNA probe-based Northern blot assay was established for VCV-M genome detection in field samples. The results showed that both the serological and nucleic acid assays could accurately and sensitively detect VCV-M in V. faba. This research represented the first confirmed expression of the putative CP of VCV-M in infected V. faba tissues. The serological and nucleic acid assays provided two complementary methods for VCV-M detection which could contribute to seed quality control and production increases of V. faba crops.
Keywords: DIG-LABELLED PROBE; POLYCLONAL ANTISERUM; VICIA CRYPTIC VIRUS M